Study of Growth Curve of Lactobacillus plantarum FNCC 0026 and Its Antibacterial Activity - Safarini Marwah; Achmad Toto Poernomo; Esti Hendradi (Universitas Airlangga, 2023)
Background: Lactobacillus plantarum is one of the lactic acid bacteria (LAB) with strong antibacterial activity. However, these bacteria show different growth for each strain. The turbidimetric bacterial growth curve approach is the most accurate, fastest, and most reproducible method for obtaining an overview of the bacterial life cycle. In addition, we also examined the antibacterial activity of each observation of the growth curve. Objective: The aim of the study was to determine the optimal incubation time with the highest biomass concentration and antibacterial activity of the Lactobacillus plantarum FNCC 0026. Method: Observations of optical density (OD) values